Biosecurity, crisis management, automation technologies and economic performance of travel, tourism and hospitality companies – A conceptual framework. Issue 1 (February 2022) - Ivanov, Stanislav Hristov; Webster, Craig; Stoilova, Elitza; Slobodskoy, Daniel
The COVID-19 pandemic of 2020 will have a significant influence on travel, tourism and hospitality (TTH) globally. With a massive reduction in tourism globally because of the health crisis, the industry will have to plan recovery and rebuilding of the industry with greater consideration of the biosecurity of customers. A critical element in the reorganisation of the industry will involve the increased incorporation of automation technologies. This article adopts a supply-side perspective and elaborates on the opportunities that automation technologies provide to TTH companies to mitigate the negative impacts of biosecurity threats on their economic performance. It discusses the costs and benefits of the incorporation of increased levels of automation, especially in regard to the benefits of the safety and health of the consumer. It elaborates on how the current pandemic would stimulate the adoption of automation technologies. Finally, the article discusses how this fit into the business models of tourism-related industries and outlines the micro- and macroeconomic implications of the greater incorporation of automation into the industry.